The effects of coenzyme Q10 and resveratrol treatment on the leukocyte counts and muscle morphology of SJL/J mice with dysferlinopathy : a qualitative microscopic investigation - Pretorius, Etheresia (University of Pretoria, 2013)
Dissertation (MSc (Cell Biology))--University of Pretoria, 2009.